Human physiology : from cells to systems - Sherwood, Lauralee. 4 0 16; 5 Cengage Learning (Firm) (Australia : Brooks/Cole, Cengage Learning, 2013)
Organized around the central theme of homeostasis, HUMAN PHYSIOLOGY helps students understand how each component of the course depends on the others and appreciate the integrated functioning of the human body. Author Lauralee Sherwood uses clear straightforward language, analogies, and frequent references to everyday experiences to help students learn and relate to the physiology concepts. The updated art program and new digital resources - including robust 3D animations - enable students to visualize important concepts and processes. By focusing on the core principles and sharing enthusiasm for the subject matter, Sherwood provides a solid foundation for future courses and careers in the health profession.--pub. desc.
Ch. 1 Homeostasis: The Foundation of Physiology Ch. 2 Cellular Physiology Ch. 3 Plasma Membrane and Membrane Potential Ch. 4 Principles of Neural and Hormonal Communication Ch. 5 Central Nervous System Ch. 6 Peripheral Nervous System: Afferent Division; Special Senses Ch. 7 Peripheral Nervous System: Efferent Division Ch. 8 Muscle Physiology Ch. 9 Cardiac Physiology Ch. 10 Blood Vessels and Blood Pressure Ch. 11 Blood Ch. 12 Body Defenses Ch. 13 Respiratory System Ch. 14 Urinary System Ch. 15 Fluid and Acid-Base Balance Ch. 16 Digestive System Ch. 17 Energy Balance and Temperature Regulation Ch. 18 Principles of Endocrinology; Central Endocrine Glands Ch. 19 Peripheral Endocrine Glands Ch. 20 Reproductive System.
Includes study cards at back of book.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Human physiology. -- 20; 20; 2